Answer:
Option C) is correct
That is the result should be in a difference of squares is
[tex](-7x+4)(-7x-4)=(7x)^2-4^2[/tex]
Step-by-step explanation:
To find the result in the form of differences in squares
Given that the expression is (-7x+4)(-7x-4)
[tex](-7x+4)(-7x-4)=(-7x)^2-4^2[/tex] ( by using the identity [tex](a+b)(a-b)=a^2-b^2[/tex] )
Here a=-7x and b=4
[tex]=(7x)^2-4^2[/tex]
Therefore [tex](-7x+4)(-7x-4)=(7x)^2-4^2[/tex] which results as a difference of squares.
Therefore Option C) is correct
That is the result should be in a difference of squares is
[tex](-7x+4)(-7x-4)=(7x)^2-4^2[/tex]